Penerapan Self-Directed Learning Melalui Sistem PBL Pada Mahasiswa Fakultas Kedokteran di Asia: Suatu Kajian Literatur - Nur Meity; Titi Savitri Prihatiningsih; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Medical student need to develop self-directed learning skills in order to promote life-long learning skill which important for medical professionality.  Rate of progression and innovation in science along with future medical world challenge incresingly strengthen self-directed learning and life-long learning as something that need to be noted.  The importance of SDL can be discerned   when American Board of Medical Specialties and World Federation for Medical Education put it as something that need to be evaluate in medical student during their time of study. The aims of this study is to gain explanation about self-directed learning implementation through PBL system and self-directed learning readiness in medical institutions in Asia.Method: This study is a literature review, that is a study been held by searching, collect, analyze and summarize a number of articles concerning  self-directed learning implementation through problem-based learning to medical students in Asia.Results: Self-directed learning readiness medical students in Asia is found inferior, especially in first year students. In addition, self-directed learning implementation for Asian context, found  that influence of lecturer exceedingly intense, where the right insight of self-directed learning will have an impact to succeed it implementation. Moreover, self-directed learning acquaintance have to be accompanied with accurate human resources management as well as support of facility and infrastructure, where the successfulness of self-directed learning implementation required entailment  and commitment of all party.